Transcriptional regulation of the human alpha2(I) collagen gene (COL1A2), an informative model system to study fibrotic diseases. - Ramirez, F; Tanaka, S; Bou-Gharios, G (2006)
During the past two decades, the human pro-alpha2(I) collagen gene (COL1A2) has emerged as an informative model in which to study the general principles that govern the transcriptional control of extracellular matrix deposition in normal and fibrotic conditions. Multiple studies have in fact delineated the genomic regions, cis-acting elements and trans-acting factors implicated in constitutive, cytokine-modulated and tissue-specific expression of COL1A2. These functional components are integrated into a regulatory network that consists of the proximal promoter, far-upstream enhancer and downstream repressor, and which operates according to two mechanisms. The first mechanism is one in which combinatorial interactions among promoter-bound proteins determine transcriptional outcome in different cellular and experimental contexts. The other mechanism is one whereby cooperative assembly of protein complexes at distantly located DNA elements directs spatiotemporal specificity. These transcriptional studies have also an additional value in translational research, in that they are providing the conceptual means to develop new animal models of and therapeutic strategies for fibrotic diseases.